Beyond – ΛCDM constraints from the full shape clustering measurements from BOSS and eBOSS. Issue 4 (22nd March 2023) - Semenaite, Agne; Sánchez, Ariel G; Pezzotta, Andrea; Hou, Jiamin; Eggemeier, Alexander; Crocce, Martin; Zhao, Cheng; Brownstein, Joel R; Rossi, Graziano; Schneider, Donald P
ABSTRACT: We analyse the full shape of anisotropic clustering measurements from the extended Baryon Oscillation Spectroscopic Survey quasar sample together with the combined galaxy sample from the Baryon Oscillation Spectroscopic Survey. We obtain constraints on the cosmological parameters independent of the Hubble parameter h for the extensions of the Lambda cold dark matter (ΛCDM) models, focusing on cosmologies with free dark energy equation of state parameter w . We combine the clustering constraints with those from the latest cosmic microwave background data from Planck to obtain joint constraints for these cosmologies for w and the additional extension parameters – its time evolution w a, the physical curvature density ω K and the neutrino mass sum ∑ m ν . Our joint constraints are consistent with a flat ΛCDM cosmological model within 68  per cent confidence limits. We demonstrate that the Planck data are able to place tight constraints on the clustering amplitude today, σ12, in cosmologies with varying w and present the first constraints for the clustering amplitude for such cosmologies, which is found to be slightly higher than the ΛCDM value. Additionally, we show that when we vary w and allow for non-flat cosmologies and the physical curvature density is used, Planck prefers a curved universe at 4σ significance, which is ∼2σ higher than when using the relative curvature density ΩK . Finally, when w is varied freely, clustering provides only a modest improvement (of 0.021 eV) on the upper limit of ∑ m ν .